Determining material properties using impact wave propagation method - Huang, Y (2017)
Mechanically testing soft materials to identify dynamic material properties remains challenging in both theory and practice. Commonly used methods, the SHPB technique for example, have very limited capacity. One of the shortcomings is the impedance mismatch between bar and specimen: conventionally metal rods are employed, which generates a weak transmitted signal; also, the stress equilibrium assumption, on which traditional time domain analysis was built, is likely to be violated due to low wave speed in soft samples. Using low-impedance polymer bars is one of the promising solutions: it removes the obstacle of the weak signal. However, the problem of stress equilibrium is not yet resolved, and complexity increased: as viscosity is introduced, material behaviours become both time and frequency dependent. Therefore, applying polymeric bars in impact settings calls for rebuilding the analytical framework and testing it in simulation and experimental environments. This work aims to answer the question: how material properties can be retrieved from an impact test? To realise this, three independent and integrated impact techniques were developed: the single rod direct impact method, the interface impact method, and the 3-rod impact method (modified SHPB). In each case, the frequency-dependent mechanical properties are derived from measurements of stress waves as they propagate in the system. The techniques were designed in a consecutive manner, but each can be used on its own. The first two techniques were fully deployed here, with complete theoretical, simulation and experimental investigations; the last technique was theoretically described, with some experimental phenomenon presented. Frequency domain analysis (FFT) was mainly adopted, important issues such as wave propagation, mechanical models, signal processing, dispersion, noise sensitivity, error analysis etc., were demonstrated throughout the journey. It is for the first time a comprehensive investigation of the single rod technique was performed combining previous and extended work; while the interface technique was brand new. The integrated framework demonstrates the robustness, accuracy, and effectiveness of utilizing wave propagation approach to identify dynamic material properties; and with proper calibration, these established works can be applied to a broad range of polymeric system-based equilibrium-free impact tests.